Study with Large Eddy Simulations of energy dissipation due to backwash flows in wave overtopping. (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Renewable energy market growth is imperative to reach a sustainable society. This necessity demands improving existing methodologies to exploit green energy sources and explore new technologies. Wave energy is one of the sources with the larger offer in power available in the oceans to be harvested; however, the remoteness and extreme conditions of the best locations to harvest wave energy have made the development of wave energy converters expensive and less attractive than other green energy sources that operate on land. Overtopping wave energy converters (OWEC) operate on the shore, facilitating their construction and maintenance. They can be integrated into coastal defences, sharing the cost of construction and their environmental impact and creating new benefits from the coastal defence. The effectiveness of an OWEC relies strongly on their ability to capture wave-overtopping volumes. The geometry of the run-up ramp (slope and shape) plays an important role in the efficiency of an OWEC. An optimum geometry for each location and wave condition needs to be found to maximise the operation of any OWEC. The efficiency of these devices, quantified by the hydraulic efficiency, must be improved to make them an attractive solution for energy conversion. Three distinguishable processes occurred on the ramp of an OWEC; the wave collapse, run-up and run-down (backwash). The first two have attracted more attention from researchers, specially oriented to the design of coastal defences, but fewer studies have analysed the impact of the backwash on the energy losses during the collapse of the waves. When an incoming wave approaches the run-up ramp, it crashes against the backwash, composed of the water volume that didn't overtop the structure in the previous wave. These interactions increase turbulences and, therefore, energy dissipation, affecting the performance of an OWEC. This study analyses the hydrodynamics during the backwash flows' and incoming waves' interaction on sloped structures. A numerical code Hydro3D, based on Large Eddy Simulations, is used to conduct the present study. As a reference condition, a structure with a freeboard high enough to not allow wave overtopping is tested; in this case, all the water that run-up the slope runs down after the water tongue reaches its highest elevation. Structures with lower freeboards are tested to allow different wave overtopping levels and backwash flows. The impact of different backwash flow conditions on energy dissipation is then evaluated. The founding of this study allows us to verify if a reduction in the backwash flows can improve the efficiency of a OWEC.